Girls’ Fashion and Khaleeji Pop Culture: The cultural fortunes of the gambūʿa, from hairdo to Internet meme - Laure Assaf (Arabian Humanities)
In the late 2000s, the gambūʿa, a beehive-style hairdo, made its apparition in the cities of the Arab Gulf. Sported by young women and characterized by a large hump above the head, it gave the impression of long and voluminous hair under the veil. The extravagant height of the hairdo and its association with the consumerist environment of Khaleeji commercial spaces soon made it the object of various condemnations. As the gambūʿa started declining in popularity, it simultaneously gained in visibility on social media, effectively turning into an Internet meme. Based on interviews conducted at the time with young Emirati women, and on an analysis of online cultural productions dedicated to the gambūʿa, this paper explores how the cultural fortunes of this controversial hairdo shed light on some of the tensions at play in contemporary Khaleeji societies, notably around representations of morality, national identity, and modernity. These tensions took on a gendered dimension, targeting specifically the category of “girls” (al-banāt). As the gambūʿa turned into a meme, however, the meanings attributed to the hairdo shifted, making it an object of online humor and ridicule rather than moral blame, and allowing young women to participate in the cultural productions around the hairdo. Ultimately, I show how the gambūʿa became an element of cultural intimacy through its integration into a regional Khaleeji pop culture.